2006
DOI: 10.1016/j.schres.2005.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnocellular contributions to impaired motion processing in schizophrenia

Abstract: Patients with schizophrenia show impairments in motion processing, along with deficits in lower level processing primarily involving the magnocellular visual pathway. The present study investigates potential magnocellular contributions to impaired motion processing in schizophrenia using a combined neurophysiological and behavioral approach. As compared to prior motion studies in schizophrenia, thresholds were determined for both incoherent and coherent visual motion. In this study, velocity discrimination thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 44 publications
7
98
4
2
Order By: Relevance
“…Visual processing deficits have been found previously in studies of patients with schizophrenia (e.g. Kim et al, 2006) and in another study related to the genetic vulnerability for developing illness (Green et al, 2006). While our data do not support the latter, it is possible that visual activation differences could implicate visual processing pathways that are relevant to the recognition of language and thus contribute to some of the changes then seen in the processing of words in frontal and temporal lobes.…”
Section: Discussioncontrasting
confidence: 67%
“…Visual processing deficits have been found previously in studies of patients with schizophrenia (e.g. Kim et al, 2006) and in another study related to the genetic vulnerability for developing illness (Green et al, 2006). While our data do not support the latter, it is possible that visual activation differences could implicate visual processing pathways that are relevant to the recognition of language and thus contribute to some of the changes then seen in the processing of words in frontal and temporal lobes.…”
Section: Discussioncontrasting
confidence: 67%
“…In our previous studies, we have consistently posited a magnocellular basis for the observed VEP P1 deficits (e.g. Foxe et al, 2005;Butler et al, 2005Butler et al, , 2007; see also Kim et al, 2005a). The VESPA scalp maps of Fig.…”
Section: Discussionsupporting
confidence: 65%
“…This result provides additional evidence for the existence of a motion processing deficit in schizophrenia (Stuve et al, 1997;Chen et al, 1999aChen et al, ,b,c, 2003aChen et al, , 2004Chen et al, , 2005Li, 2002;Slaghuis et al, 2005;Kim et al, 2006). More importantly, at high contrast, schizophrenic patients exhibit reduced centersurround suppression.…”
Section: Discussionmentioning
confidence: 51%